Enhance cycling performance of LiMn2O4 cathode by Sr2+ and Cr3+ doping. (March 2015) - Liang, X.; Zeng, S.; Liu, Y.; Shi, L.; Liu, T.
Abstract : Spinel LiSr0·1 Cr0·1 Mn1·8 O4 was synthesised by high temperature solid state method in order to enhance the electrochemical performance. The LiSr0·1 Cr0·1 Mn1·8 O4 (LSCMO) materials were characterised by X-ray diffraction (XRD), scanning electron microscopy (SEM) and electrochemical tests. The XRD and SEM studies confirm that LSCMO had spinel crystal structure with a space group of Fd3m, and the particle of LSCMO shows irregular shape. The cyclic voltammetry data illustrated that the heavy current charge–discharge performance of LMO was improved by Sr 2+ and Cr 3+ doping. The galvanostatic charge–discharge of LSCMO cathode materials was measured at 1, 5, 10 and 20 C. The results indicated that LSCMO improved the capacity retention.